Online Business Practices: A Study of Islamic Business Ethics Perspective in Indonesia - Saputra, Arief Dwi; Rahmatia, Alfina; Wahyuningsih, Sri Handari; Azhar, Andi (JURNAL PENELITIAN, 2022)
Islamic business ethics is the implementation of the basic principles of Islamic-based business, which the Al-Qur'an and As-Sunnah guide. This study will explain online business practices in Indonesia by observing an Islamic perspective. This study uses a qualitative strategy by investigating Islamic business ethics in online business practices in Indonesia through information and document data collection in the form of reputable online media news. Data were analyzed and managed using Nvivo plus 12; then, conclusions were drawn. The aim of this study is achieved by finding that there are still many ethical violations in online business practices from a religious perspective. The findings also reveal that Islamic values are rarely used in business implementation because some violations occur not based on the intention of worship and are not based on Islamic principles such as At-Tauhid, Al-Amanah, As-Sidq, Al-Adalah, At-Ta'awun, Al-Maslahah, At-Taradi, and Al-Akhlaq Al-Karimah. This also proves that online business practices are still oriented to worldly aspects. The implication of the results of this study explains that doing business activities from an Islamic perspective contains principles that comprehensively govern ethics. So that the purpose of doing business is not solely for the interests of worldly welfare, but for the welfare of the ukhrawi in the pleasure of Allah SWT, and the benchmarks are al-Qur'an and al-Hadith.